METHODOLOGY FOR IMPROVING PHYSICAL TRAINING OF CADETS OF THE MINISTRY OF EMERGENCY SITUATIONS ACADEMY - Boymatov X.X.; Talipov G.O.; Matniyoz U.A.; Maratovich J.J. (Proximus Journal Publishing, 2024)
The organization and conduct of physical education events, sports events is established in the law of the Republic of Uzbekistan "on Physical Education and sports". Training of specialists for conducting mass physical education and sports events is carried out by universities of physical education in the direction of "Organization of mass sports events"
Keywords: Olympic and national sports; In mass sports; professional and physical training